Analysis of the Needs for Developing Papua Context-Based Literacy Teaching Materials for ANBK Preparation: A Literature Review - Asweni, Dirga Firhan Nuari; Wabiser, Yan Dirk; Amsad, Lusia Narsia (Interdisciplinary Journal of Social Sciences, 2024)
This study aims to analyze the needs and strategies for developing Papuan context-based literacy teaching materials in preparation for the National Computer-Based Assessment (ANBK). Following a systematic literature review method, this study analyzed journal articles, reference books, policy documents and research reports published in the 2019-2024 timeframe. The results showed three main findings: (1) the condition of literacy in Papua requires a socio-cultural context-based approach, not just technical reading and writing skills; (2) the implementation of ANBK in the 3T (Frontier, Outermost, Left Behind) areas of Papua faces specific challenges related to technological infrastructure, teacher readiness, and student understanding of the context of the questions; (3) the development of effective teaching materials needs to integrate three aspects, namely the local context that accommodates Papuan cultural wisdom, pedagogical approaches that support learning independence, and a continuous formative evaluation system. This study recommends the development of teaching materials that integrate national curriculum standards with local Papuan contexts to increase the effectiveness of ANBK preparation.